Pengembangan konsep pembelajaran etika umum berlandaskan pancasila untuk mengurangi tindakan korupsi - Khamidah, Lailatul LailatulKhamidah (Maliki Interdisciplinary Journal, 2026)
This research intends to create an ethical educational model rooted in Pancasila, aiming to serve as a strategic teaching method to promote integrity and deter corrupt practices in learning environments. The importance of this research arises from the ongoing issue of corruption, which has developed into a systemic concern within government bodies as well as a social and cultural dilemma ingrained in everyday activities. Pancasila, the guiding philosophy of Indonesia, includes five fundamental values—Faith in God, Humanity, Unity, Democracy, and Justice—which act as ethical foundations for building an anti-corruption character. This study explores how these principles can be embedded into a structured educational model that meets the current needs of education. The developed model features three main components. The first component focuses on enhancing moral consciousness, which improves students capacity to recognize and assess actions that are morally questionable or could lead to corruption. The second component emphasizes the establishment of integrity-driven behavior, facilitated through context-based learning, exemplification by teachers, and active involvement from students in reflective ethical practices. The third component entails the application of Pancasila principles to ethical decision-making, especially using case-based learning and group discussions. This study employs a qualitative methodology that includes curriculum content assessment, interviews with educators, and observational studies in classrooms. The results reveal that the intentional incorporation of Pancasila values into educational practices boosts students’ moral development, legal consciousness, and dedication to anti-corruption values. Conclusively, a Pancasila-centered ethical learning framework provides a strong basis for character education and has the potential to significantly enhance a sustainable culture against corruption in the country and educating children about how to become Indonesian citizens,from primary school onwards,and consistently promoting a culture of anti-corruption to support the government in its efforts to combat corruption.